PENGARUH IKLAN DAN KUALITAS PRODUK TERHADAP MINAT MEMBELI SEPEDA MOTOR (Studi Pada Honda Pcx di Kota Denpasar) - Pande Kadek Aprilyana Dewi; I Gusti Agung Ngurah Gede Eka Teja Kusuma; I Gede Rihayana (EMAS, 2021)
Purchasing interest is the tendency of consumers to buy a brand or take actions related to purchasing decisions as measured by the likelihood of consumers making a purchase. Consumer buying interest will arise when consumers are already interested or already feel confident about the quality of the product in the brand. In determining the choice, a consumer will of course be faced with a variety of information from a product. Currently consumers do not need to worry, because to find out various kinds of information about a product, consumers can look for it online or with various other media. One of the sophisticated media that can attract consumers to buy a product is the use of advertising. In modern marketing activities, advertising is part of the promotion mix, together with personal selling, publicity and trade promotion activities. Meanwhile, from the perspective of marketing and economic communication, the promotion mix is part of the marketing mix activities. The phenomenon that occurs at Honda is that even though it is at the forefront of sales of automatic motorbikes, there are several Honda brands that have experienced a decline in sales in 2019, especially the Honda Pcx type. The population in this study were all consumers of Honda Pcx motorbikes who visited Astra Motor. The sample in this study were 96 respondents who were determined based on the accidental sampling method. The analytical tool used to test the hypothesis is Multiple Linear Regression Analysis. The results showed that advertising and product quality had a positive and significant effect on buying interest. Further research can develop this research by using other variables which in theory have an influence on buying interest.